Development of Interactive Teaching Materials at SMP Negeri 3 Nusawungu Cilacap Regency - Idah Rahmayanti (Proceedings Series on Social Sciences & Humanities, 2022)
The purpose of writing is to develop interactive teaching materials as material for teachers and students in the implementation of the learning process. Therefore, it is necessary to develop innovative teaching materials, so that students can achieve mastery learning. The research subjects were teachers of SMP N 3 Nusawungu grades 7, 8 and 9. Data collection tools were used through observation and interviews. The research data analysis technique is interactive analysis which includes data collection, data presentation and conclusions. The results showed that: there was awareness of the teachers of SMP Negeri 3 Nusawungu in developing interactive teaching materials. It can be seen that the teacher is able to create a variety of teaching materials with the style and competence of each teacher. The tangible form appears in the form of various interactive teaching materials.